Confirmation and evaluation of performance measurement model for the Thai frozen shrimp chain - Sirirat Pungchompoo (2018)
© 2015, © Emerald Group Publishing Limited. Purpose: – The purpose of this paper is to investigate and evaluate the new performance measurement model for the Thai frozen shrimp chain. Design/methodology/approach: – The performance measurement model was developed by the combination method between a structural equation modeling and an analytical hierarchy process, which the method confirmed and proved the construction of the framework and identified the important key performance indicators of the chain from different supply chain members’ point of views. Findings: – The results showed that the model is reliable and valid as well as being theoretically acceptable on the basis of performance measurement foundations. Furthermore, the financial and the customer perspectives are demonstrated as the first to be prioritized in order to evaluate the performance. Research limitations/implications: – Two limitations should be considered. First, small sample size of this study is a limitation. Hence, further study should consider on enough sample size. A next limitation, different points of view from participants has effect on factor loading which represented minus value on the research model. Therefore, the future research should apply several techniques, such as the fuzzy set and data envelopment analysis. Originality/value: – The contribution of this study is the new performance measurement model which based on the integrated conceptual ideas and the synthesizing methods for evaluating the Thai frozen shrimp chain.